Perancangan Aplikasi String Matching Dalam Pencarian Makanan Pantanagn Untuk Penderita Penyakit Kanker Dengan Algoritma Berry-Ravindran Berbasis Android - M Zulhasmi Lubis (KLIK: Kajian Ilmiah Informatika dan Komputer, 2020)
body or human body. Each food will contain substances such as carbohydrates, fat, protein, vitamins, minerals and water, but there are also foods that should not be eaten and consumed because the food eaten cannot be eaten by people who have cancer when eaten with large amounts bad for health and disease will extend the duration of the cancer. In the settlement the author uses the Berry-Ravindran Algorithm, Berry-Ravindran algorithm is a matching algorithm which is a combination of Quick Search algorithm and Zhu-Takaoka algorithm. Berry Ravindran is one of the string matching algorithms that can do a search and take into account the shift in bad characters whose shift values are obtained from the preprocessing phase. Berry Ravindran's algorithm will begin to shift from left to right in search of words and sentences that can be done quickly and easily. The design that is expected later this application of taboo food for cancer patients can run well in all devices and versions of Android smartphones, and the application designed It is also expected to be able to help the community, especially in cancer patients in finding dietary foods based on cancer that they suffer